Geographical pecularities of the influence of the climatic conditions upon mountain-and-kettle landscapes of The Great Caucasian northern slope - V. V. Bratkov; Z. V. Ataev (Юг России: экология, развитие)
The authors of the article analyze the changes of the air temperature, precipitation quantity and conditions of moisturizing in mountain-and-kettle landscapes of the northern slope of the Great Caucasus, according to the data of “Kislovodsk”, “Shatoy”, “Akhty” weather stations.